A corpus-based translation study on Italian verb-particle constructions translated into Spanish. The case of Lessico famigliare - Artusi, Andrea (MonTi Monografías de Traducción e Interpretación, 2018)
Verb-particle constructions (VPCs) are considered to be a very productive linguistic phenomenon within the Italian language, especially in spontaneous and informal dialogues. On the contrary, in the Spanish language the productivity of such constructions appears to be low. In order to figure out which linguistic patterns seem to be more frequent while translating Italian verb-particle constructions into Spanish, a parallel corpus will be analysed. The corpus consists of the Italian novel Lessico famigliare (by Natalia Ginzburg, 1963) and its translation into Spanish. First, a list of the VPCs contained in the source text will be provided. Secondly, we will show which linguistic patterns are used in the translation, elucidating the reasons why they tend to appear, by means of a cognitive approach. Finally, some translation errors will be highlighted. The possible causes that resulted in such errors will lead us to allege that VPCs should be considered as translation problems.